Impact of Metabolic Syndrome Components on Carotid Intima-Media Thickness as a Marker of Subclinical Atherosclerosis - Aamir Siddique, Shaoib Ahmed Zia, Muhammad Zahid Ali Raza, Tayyab Mohyuddin, Arslan Aslam Chahudhary, Faiza Altaf, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Metabolic Syndrome (MetS), characterized by a cluster of interrelated cardiovascular risk factors including central obesity, hypertension, dyslipidemia, and hyperglycemia, plays a pivotal role in the development of atherosclerosis. Carotid Intima-Media Thickness (CIMT) is a well-established, non-invasive surrogate marker for subclinical atherosclerosis and an early predictor of future cardiovascular events. Objective: This study aimed to evaluate the impact of individual components of Metabolic Syndrome on CIMT, with a particular focus on gender-specific variations in vascular risk. Methodology: A cross-sectional study was conducted from April 2022 to May 2023 at two tertiary care hospitals in Punjab, Pakistan: Chahudhary Pervaiz Elahi Institute of Cardiology and Hawa Memorial Hospital, Wazirabad. A total of 150 adult patients (75 males and 75 females), aged 30 to 65 years, who met the NCEP ATP III diagnostic criteria for MetS were enrolled. Demographic data and fasting blood samples were collected to assess body mass index (BMI), waist circumference, blood pressure, fasting glucose, triglycerides, and HDL-C levels. CIMT was measured using high-resolution B-mode ultrasonography. Gender-based comparisons were analyzed using independent t-tests, with statistical significance set at p < 0.05. Results: Males demonstrated significantly greater waist circumference (102.07 ± 7.53 cm vs. 93.78 ± 8.59 cm, p < 0.001) and lower HDL-C levels (37.30 ± 5.06 mg/dL vs. 44.78 ± 5.33 mg/dL, p < 0.001) compared to females. Although CIMT was higher in males (0.74 ± 0.08 mm) than in females (0.71 ± 0.09 mm), the difference did not reach statistical significance (p = 0.0607). Conclusion: Central obesity and low HDL-C were identified as major contributors to early vascular alterations, particularly among male patients with MetS. Gender-specific metabolic risk profiling and incorporation of CIMT assessment may enhance early detection and prevention of atherosclerotic cardiovascular disease in at-risk populations. Keywords: Metabolic Syndrome, Carotid Intima-Media Thickness, Subclinical Atherosclerosis, HDL-C, Central Obesity, Cardiovascular Risk